Electrooxidation of dopamine using MoS2-Ag conductive ink on screen-printed electrodes for electrochemical sensing - Mphuthi, Ntsoaki; Sikwhivhilu, Lucky Mashudu; Ray, Suprakas Sinha; Ntsendwana, Bulelwa (Frontiers in Sensors, 2025)
Abnormal dopamine (DA) levels in the human body are associated with severe health conditions, making their accurate detection crucial for early diagnosis and monitoring. Therefore, the development of a highly sensitive electrochemical sensor for DA detection is of significant importance in physiological, biochemical, pharmaceutical, and medical applications. In this study, screen-printed electrodes (SPEs) were fabricated using MoS2-based conductive inks containing varying concentrations of silver nanoparticles (Ag NPs) to enhance electrocatalytic activity. The ink composition included ethyl cellulose and polyvinylpyrrolidone (PVP) as binders, providing structural integrity and adhesion, while terpineol was used as the solvent to achieve the desired viscosity for smooth and consistent printing. The printed electrodes underwent comprehensive electrochemical characterization to assess their performance, including stability, reproducibility, and sensitivity. Electrochemical analysis revealed that the SPCE/MoS2-Ag,4 electrode exhibited the best sensing characteristics due to the optimized interaction between MoS2 and Ag NPs, which facilitated improved electron transfer and enhanced detection capability. The electroanalytical performance of the sensors was assessed using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and chronoamperometry. The SPCE/MoS2-Ag,4 sensor demonstrated a wide linear detection range from 0.01 to 0.08 mM and an exceptionally low limit of detection (LOD) of 0.016 μM for DA. Additionally, the sensor exhibited excellent reproducibility, high sensitivity, and strong selectivity, making it a promising candidate for reliable dopamine detection in biomedical and clinical applications.